Dietary intakes, food behaviours and health indicators among Métis youth in Manitoba, Canada - Chantal Perchotte; Olena Kloss; Joyce Slater; Alan Katz; Bhanu Pilli; Aynslie Hinds; Marcelo L Urquia; Julianne Sanguins; Chris Green; Jaime Cidro; Dan Chateau; Nathan Nickel; et al. (Public Health Nutrition)
Abstract